Dead in the doorway - Kelly, Diane (Kelly, Diane. House-flipper mystery, 2020)
"Whitney Whitaker has scored the perfect piece of real estate: a ramshackle white Colonial at the top of a hill with views of downtown Nashville. What more could a self-taught home-improvement maven and occasional house-flipper ask for? Ideally, the property of Whitney's dreams would not have come with a dead body blocking the entrance to the foyer. But Whitney, always quick to take heavy-duty matters into her own hands, also happens to be a skilled amateur sleuth. So that helps."--Provided by publisher.